Raltegravir cerebrospinal fluid concentrations in HIV-1 infection. - Aylin Yilmaz (PLoS ONE, 2009)
Raltegravir is an HIV-1 integrase inhibitor currently used in treatment-experienced HIV-1-infected patients resistant to other drug classes. In order to assess its central nervous system penetration, we measured raltegravir concentrations in cerebrospinal fluid (CSF) and plasma in subjects receiving antiretroviral treatment regimens containing this drug.Raltegravir concentrations were determined by liquid chromatography tandem mass spectrometry in 25 paired CSF and plasma samples from 16 HIV-1-infected individuals. The lower limit of quantitation was 2.0 ng/ml for CSF and 10 ng/ml for plasma.Twenty-four of the 25 CSF samples had detectable raltegravir concentrations with a median raltegravir concentration of 18.4 ng/ml (range, <2.0-126.0). The median plasma raltegravir concentration was 448 ng/ml (range, 37-5180). CSF raltegravir concentrations correlated with CSF:plasma albumin ratios and CSF albumin concentrations.Approximately 50% of the CSF specimens exceeded the IC(95) levels reported to inhibit HIV-1 strains without resistance to integrase inhibitors. In addition to contributing to control of systemic HIV-1 infection, raltegravir achieves local inhibitory concentrations in CSF in most, but not all, patients. Blood-brain and blood-CSF barriers likely restrict drug entry, while enhanced permeability of these barriers enhances drug entry.